2006
DOI: 10.1016/j.molcel.2006.06.010
|View full text |Cite
|
Sign up to set email alerts
|

A Basal Promoter Element Recognized by Free RNA Polymerase σ Subunit Determines Promoter Recognition by RNA Polymerase Holoenzyme

Abstract: During transcription initiation by bacterial RNA polymerase, the sigma subunit recognizes the -35 and -10 promoter elements; free sigma, however, does not bind DNA. We selected ssDNA aptamers that strongly and specifically bound free sigma(A) from Thermus aquaticus. A consensus sequence, GTA(C/T)AATGGGA, was required for aptamer binding to sigma(A), with the TA(C/T)AAT segment making interactions similar to those made by the -10 promoter element (consensus sequence TATAAT) in the context of RNA polymerase holo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
116
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(122 citation statements)
references
References 46 publications
4
116
0
Order By: Relevance
“…Thus, the GGGA motif is a bona fide basal promoter element for T. aquaticus RNAP. Indeed, we found that similar motifs are present in natural promoters and increase stability of promoter complexes of RNAPs from T. aquaticus and related bacteria (8). Bioinformatics analysis suggested that up to 33% of predicted promoters in the genome of Thermus thermophilus contain GGGA-like motifs.…”
mentioning
confidence: 85%
See 3 more Smart Citations
“…Thus, the GGGA motif is a bona fide basal promoter element for T. aquaticus RNAP. Indeed, we found that similar motifs are present in natural promoters and increase stability of promoter complexes of RNAPs from T. aquaticus and related bacteria (8). Bioinformatics analysis suggested that up to 33% of predicted promoters in the genome of Thermus thermophilus contain GGGA-like motifs.…”
mentioning
confidence: 85%
“…Bioinformatics analysis suggested that up to 33% of predicted promoters in the genome of Thermus thermophilus contain GGGA-like motifs. In contrast, no preference for such motifs was found in E. coli promoter sequences (8).…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…1): the UP element (bound by the C-terminal domains of the two ␣ subunits); the Ϫ35 hexamer (bound by region 4.2); the extended Ϫ10 element (bound by region 3.0); and the Ϫ10 hexamer (bound by region 2.3-2.4). Recently, an additional element immediately downstream of the Ϫ10 hexamer, within the discriminator region, was proposed to bind to region 1.2 (3,4).…”
mentioning
confidence: 99%